2014
DOI: 10.1136/neurintsurg-2014-011306
|View full text |Cite
|
Sign up to set email alerts
|

Micro Vascular Plug (MVP)-assisted vessel occlusion in neurovascular pathologies: technical results and initial clinical experience

Abstract: To the best of our knowledge, this is the first series reporting the use of MVP in neurovascular disease. Use of this device may be associated with shorter procedural times and cost savings in comparison with the use of microcoils for vessel occlusion. Our experience shows that MVP can have unique applications in neurovascular pathologies and it complements other occlusive devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 5 publications
(2 reference statements)
1
26
0
Order By: Relevance
“…It is possible to safely occlude the lingual arteries over a relatively long segment. Although recently introduced devices have been reported to facilitate safe vessel occlusion of human arteries over a short segment,24 25 the safety of deconstructive approaches in these circumstances has not been fully elucidated. A longer period of follow-up time after treatment may have resulted in improved occlusion scores, but this was not studied in this work.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to safely occlude the lingual arteries over a relatively long segment. Although recently introduced devices have been reported to facilitate safe vessel occlusion of human arteries over a short segment,24 25 the safety of deconstructive approaches in these circumstances has not been fully elucidated. A longer period of follow-up time after treatment may have resulted in improved occlusion scores, but this was not studied in this work.…”
Section: Discussionmentioning
confidence: 99%
“…An MVP has shown immediate and stable target vessel occlusion without complications [3]. A two center pilot study by Pellerin et al in 14 patients showed successful navigation, deployment, and occlusion of tortuous, and small 1-3 mm diameter vessels with only 1 MVP per target artery [5].…”
Section: Discussionmentioning
confidence: 98%
“…The operator can inject contrast through the catheter before detaching the plug with the device deployed and then resheath it for precision placement. The MVP device has demonstrated promise and efficacy in neurovascular disease [3].…”
Section: Dear Editormentioning
confidence: 99%
“…The Medtronic Micro Vascular Plug™ (MVP) is an FDA approved and CE marked product. It has been used for vascular embolization in neuro‐interventional and other interventional radiology procedures, mostly in adults . Since the MVP is a large diameter vascular occlusion device that can be delivered through a microcatheter, it may be ideally suited for use in children with CHD.…”
Section: Introductionmentioning
confidence: 99%
“…It has been used for vascular embolization in neuro-interventional and other interventional radiology procedures, mostly in adults. [14][15][16][17][18] Since the MVP is a large diameter vascular occlusion device that can be delivered through a microcatheter, it may be ideally suited for use in children with CHD. The objective of this study was to describe the early, multi-center clinical experience with the MVP in children with underlying CHD undergoing vascular embolizations.…”
Section: Introductionmentioning
confidence: 99%